Coproducing a library of videos to support families caring for children with gastrostomies: A mixed‐methods evaluation with family carers and clinicians. (9th February 2022) - Page, Bethan; Lee, Alex C. H.; Harrop, Emily J.; Beale, Tania; Sharrard, Alison; Yeung, Nick; Vincent, Charles A.
Abstract: Introduction: Many families now perform specialist medical procedures at home. Families need appropriate training and support to do this. The aim of this study was to evaluate a library of videos, coproduced with parents and healthcare professionals, to support and educate families caring for a child with a gastrostomy. Methods: A mixed‐methods online survey evaluating the videos was completed by 43 family carers who care for children with gastrostomies and 33 healthcare professionals (community‐based nurses [ n  = 16], paediatricians [ n  = 6], dieticians [ n  = 6], hospital‐based nurses [ n  = 4], paediatric surgeon [ n  = 1]) from the United Kingdom. Participants watched a sample of videos, rated statements on the videos and reflected on how the videos could be best used in practice. Results: Both family carers and healthcare professionals perceived the video library as a valuable resource for parents and strongly supported the use of videos in practice. All healthcare professionals and 98% ( n  = 42) of family carers agreed they would recommend the videos to other families. Family carers found the videos empowering and easy to follow and valued the mixture of healthcare professionals and families featured in the videos. Participants gave clear recommendations for how different video topics should fit within the existing patient pathway. Discussion: Families and healthcare professionals perceived the videos to be an extremely useful resource for parents, supporting them practically and emotionally. Similar coproduced educational materials are needed to support families who perform other medical procedures at home. Patient or Public Contribution: Two parent representatives attended the research meetings from conception of the project and were involved in the design, conduct and dissemination of the surveys. The videos themselves were coproduced with several different families.